If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -5s + -48 = -1a Reorder the terms: -48 + -5s = -1a Solving -48 + -5s = -1a Solving for variable 's'. Move all terms containing s to the left, all other terms to the right. Add '48' to each side of the equation. -48 + 48 + -5s = 48 + -1a Combine like terms: -48 + 48 = 0 0 + -5s = 48 + -1a -5s = 48 + -1a Divide each side by '-5'. s = -9.6 + 0.2a Simplifying s = -9.6 + 0.2a
| 3(4x-17)=3(x+7) | | 36x-45= | | -2(-7n+1)=5n-10 | | 46+21=11g | | 10-5m=45 | | 3(5y-5)-4= | | 17-11=2(x-7) | | 0.7t-3.2=1.7 | | h=-16t^2+60t+1 | | 7x+19-4x+4= | | -(3x+2)= | | -2-y=9 | | -105=8x | | 15x^2-x-54=0 | | 9j+2-j=8 | | ln(5)=ln(x+2)-ln(2) | | -6/-6 | | 0.5+6.4=4.9-18 | | 5v=9 | | 5x-16=x+6 | | -9x+5=-103 | | 3.2x+2.6=23 | | AX^2=2AX | | 7(x-3)=3x+15 | | 4(2x-3/4)=53 | | 455=O | | -3/4=c+7/10 | | 444/100-1/12=x | | 95=O | | x/2-6=-4 | | 4+m/5=8 | | 13(ab)= |